Development of Realistic Mathematics Education-Based Student Worksheets to Enhance Self-Regulated Learning in Social Arithmetic - Endah Nawang Wulan; Karyati Karyati (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aims to design and develop student worksheets based on the Realistic Mathematics Education (RME) approach to enhance students’ self-regulated learning (SRL), specifically in the context of social arithmetic. A research and development design was employed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study involved 48 grade VII students from two schools: MTs Muslimat NU and SMP Muhammadiyah Palangkaraya. Instruments included RME-based worksheets and an SRL questionnaire. Effectiveness was analyzed using a one-sample t-test with IBM SPSS 21. The worksheet was validated by experts and achieved a score of 94 out of 100, categorized as “very valid.” Practicality results showed high usability: teachers rated it 31.5/35 (“very practical”) and students 44.95/60 (“practical”). After implementation, students’ SRL improved from 44.44% to 83.33%, an increase of 38.89%. The one-sample t-test showed a significance value of 0.001 ( 0.05), indicating the worksheet’s effectiveness. The mean student questionnaire score was 65.16, classified as “effective.” The developed RME-based worksheets are valid, practical, and effective in supporting students’ independent learning. They promote meaningful engagement with mathematical content, improve comprehension of social arithmetic, and help students monitor their own progress. These results highlight the potential of RME in fostering student-centered mathematics learning.